2016
DOI: 10.1002/jbm.a.35799
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of antibacterial activity of the chitosan‐based hydrogel films using central composite design

Abstract: In the present study, hydrogel films composed of chitosan-poly(vinyl alcohol)-gelatin-thyme honey were successfully prepared by casting method, and their anti-bacterial properties were modeled and optimized. Antibacterial properties of the prepared films were analyzed by applying agar diffusion method. Staphylococcus aureus and Pseudomonas aeruginosa were tested as Gram-positive and Gram-negative bacteria, respectively. In order to obtain the composition of the film with maximum inhibition zone against both ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…The ANOVA results for Y1 and Y2 provided F values of 50.65 and 18.78, as compared to the critical values from the cutoff points for the F distribution (=0.05), i.e., 3.9 and 4.1, respectively. These F values suggest that the derived quadratic models had significant influences on the responses [ 8 ]. R 2 and the adjusted R 2 values for Y1 were 98.92% and 96.96%, and for Y2 were 91.25% and 86.40%, respectively, which demonstrate the accuracy of the tests and the fitness of the results with the proposed models [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ANOVA results for Y1 and Y2 provided F values of 50.65 and 18.78, as compared to the critical values from the cutoff points for the F distribution (=0.05), i.e., 3.9 and 4.1, respectively. These F values suggest that the derived quadratic models had significant influences on the responses [ 8 ]. R 2 and the adjusted R 2 values for Y1 were 98.92% and 96.96%, and for Y2 were 91.25% and 86.40%, respectively, which demonstrate the accuracy of the tests and the fitness of the results with the proposed models [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan-PVA hydrogels have been widely used as wound dressing, and a series of studies have shown these composite materials enhanced wound healing as well as antibacterial activities. 53,[113][114][115][116][117] Related research also proved that chitosan-PVA hydrogel exhibited a good bactericidal activity against E. coli. The hydrogel with greater chitosan concentration (60% and 80%), had a better cell viability, proliferation, and blood clotting ability.…”
Section: Chitosan-based Hydrogels As Wound Dressingmentioning
confidence: 99%
“…114 If honey or bee venom was added into the chitosan-PVA hydrogel, it strengthened the anti-inammatory effect and antibacterial activity, hence, enhanced wound healing. [115][116][117] All of these researches indicated chitosan-PVA hydrogels have excellent potential as wound dressings.…”
Section: Chitosan-based Hydrogels As Wound Dressingmentioning
confidence: 99%
“…However, given that Ag ions have been proven to be highly toxic, wound healing is often delayed. Thus, modified chitosan or chitosan derivatives and new alginate‐based antibacterial hydrogels dressings have attracted increased research attention …”
Section: Methodsmentioning
confidence: 99%
“…Thus, modified chitosan or chitosan derivatives and new alginate-based antibacterial hydrogels dressings have attracted increased research attention. [9][10][11][12][13] Despite the advancements and the wide range of dressings available, wound management remains extremely challenging because of the susceptibility of a wound to bacterial infection. [14] Especially, diagnosis of bacterial infection is not straightforward and speed of detection is essential in clinical conditions.…”
mentioning
confidence: 99%